Bidimensional interpolation operators of finite element type and degree of exactness two - Roşca, Daniela (Rev. Anal. Numér. Théor. Approx., 2005)
For a given arbitrary triangulation of \(R^2\), we construct an interpolating operator which is exact for the polynomials in two variables of total degree \(≤ 2\). This operator is local, in the sense that the information around an interpolation node is taken from a small region around this point. We study the remainder of the interpolation formula.